Healthcare Cost and Impact of Persistent Orofacial Pain: The DEEP Study Cohort. (September 2016) - Durham, J.; Shen, J.; Breckons, M.; Steele, J.G.; Araujo-Soares, V.; Exley, C.; Vale, L.
Few data are available on the healthcare costs of those suffering from persistent orofacial pain (POFP). This cohort and cost analysis study examined the direct costs of POFP from the perspective of the healthcare provider (specifically, the UK National Health Service) in 2012 pounds sterling and sought to identify whether dichotomized (high, IIb to IV; low, 0 to IIa) graded chronic pain scale (GCPS) status is predictive of the total cost of healthcare over the last 6 mo. The healthcare utilization data of 198 patients with POFP were collected using a structured interview and a validated "use of services and productivity" questionnaire. Unit costs were used with these utilization data to calculate direct healthcare costs in 3 categories: consultation, medication, and appliances and interventions. Consultation costs were a significant proportion of cumulative healthcare cost ( P < 0.001). Dichotomized GCPS status was predictive of increased healthcare cost over the last 6 mo, accounting for an average increase of £366 (95% confidence interval, 135 to 598; P < 0.01) when moving from a low GCPS status to a high GCPS status. Given the predictive capability of dichotomized GCPS status and the success of stratified models of care for other persistent pain conditions, dichotomized GCPS status may offer an opportunity to help determine stratification of care for patients with POFP.